The effectiveness of functional training on static balance, dynamic balance and flexibility of females with intellectual disability - SAKINEH FARROKHIAN; GHORBAN HEMATI ALAMDARLOO; ENAYATOLLAH ASADMANESH (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: Children with intellectual disability (ID) have less balance and flexibility than typically developing peers. The aim of this study was to determine the effectiveness of functional training on static balance, dynamic balance and flexibility of female students with intellectual disability. Material/Methods: The research method was pre-test - post-test with a control group. The statistical population consisted of all female students with ID in elementary school of Shiraz studying under the auspices of the Special Education Organization in 2018-2019. The participants included 30 female students with ID selected through convenience sampling and randomly assigned to the experimental (n = 15) and control (n = 15) groups. The experimental group received functional training for 15 sessions, while the control group did not receive any intervention. The Single leg stance test was used for measuring static balance; the Tandem gait test was used for measuring dynamic balance, and the Sit and Reach test was used for measuring flexibility. The collected data were analyzed using ANCOVA. Results: The results showed that functional training had a significant effect on static and dynamic balance and flexibility of female students with intellectual disability (p<0.05). Conclusions: It is recommended that functional training be given special attention by educators, teachers and child education experts.